A Study on Impact of Socio Economic Profile on Investment Pattern of Salaried and Business People in Coimbatore City - Devi, Chitra (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
In recent times, the investment companies have emerged as the most dynamic segment in the Indian financial system. Reforms in the Indian economic system and the opening up of the economy have been the reasons for the tremendous growth in the Indian capital market. This study analyzes the impact of socio economic variables on the attitude of investors towards investments. Apart from this, it also focuses on the benefits delivered by savings to investors. To achieve, 100 respondents of Coimbatore city, having different socio economic profiles were surveyed. The results also highlight that certain factors like education level, awareness about the financial system, age of invertors etc make significant impact while deciding on the investment pattern for investment. Further, it is observed that the level of income also influences the investment decisions. Higher income group shows relatively high preference towards investment in share market, conversely lower and average income group shows keen preference towards insurance and banks as the most preferred investment avenues